2023
DOI: 10.1136/bmjopen-2022-064394
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-supported behavioural weight loss treatment in adults with severe obesity: study protocol for an exploratory randomised controlled trial (SmartBWL)

Abstract: IntroductionBehavioural weight loss (BWL) treatment is the standard evidence-based treatment for severe obesity (SO; body mass index ≥40.0 kg/m2or ≥35.0 kg/m2with obesity-related comorbidity), leading to moderate weight loss which often cannot be maintained in the long term. Because weight loss depends on patients’ use of weight management skills, it is important to support them in daily life. In an ecological momentary intervention design, this clinical trial aims to adapt, refine and evaluate a personalised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…An increasing significance to the assimilation of telepsychiatry into health systems is driven by the emergence of multiple mobile applications that provide additional data concerning patients’ health and generating tighter communication between the different caretakers, and even informal caregivers . 42 Thus, apps that are unique to telepsychiatry could facilitate multiple advancements such as joint meetings of a group of caretakers exchanging ideas and data, 43 , 44 streaming of data collected from mobile-based apps that provide data concerning voice modulation, movement, money spending, social interactions, frequency of phone calls, and other data, 45 48 and also enable psychotherapeutic groups sessions 49 , 50 omitting the logistical requirements within a clinical facility.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing significance to the assimilation of telepsychiatry into health systems is driven by the emergence of multiple mobile applications that provide additional data concerning patients’ health and generating tighter communication between the different caretakers, and even informal caregivers . 42 Thus, apps that are unique to telepsychiatry could facilitate multiple advancements such as joint meetings of a group of caretakers exchanging ideas and data, 43 , 44 streaming of data collected from mobile-based apps that provide data concerning voice modulation, movement, money spending, social interactions, frequency of phone calls, and other data, 45 48 and also enable psychotherapeutic groups sessions 49 , 50 omitting the logistical requirements within a clinical facility.…”
Section: Discussionmentioning
confidence: 99%
“…Morbid obesity (BMI > 40 kg/m 2 or BMI > 35 kg/m 2 combined with other obesity-related diseases) can lead to hypertension, hyperlipidemia, diabetes, heart disease, etc., which can seriously affect people's physical health and cause a huge social burden. [14] As a widely used bariatric surgery, LSG was discussed in this study. Studies have shown that LSG has high…”
Section: Discussionmentioning
confidence: 99%
“…Morbid obesity (BMI > 40 kg/m 2 or BMI > 35 kg/m 2 combined with other obesity-related diseases) can lead to hypertension, hyperlipidemia, diabetes, heart disease, etc., which can seriously affect people’s physical health and cause a huge social burden. [14] As a widely used bariatric surgery, LSG was discussed in this study. Studies have shown that LSG has high safety, lasting postoperative weight loss, and can effectively alleviate the related comorbidities in morbidly obese patients, thus significantly improving the quality of life of morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%